Pre-pandemic family resources and child self-regulation in children’s internalizing problems during COVID-19: a multi-level social-ecological framework for emotional resilience - Chen, Luxi; Yeung, Wei-Jun Jean (Frontiers in Psychology, 2023)
Introduction Children’s psychological adjustment to adverse events can be determined by multiple risk and resilience factors. This study explored multi-level protective factors against children’s internalizing problems and investigated the mechanism regarding how diverse environmental and child-level resources influence children’s mental health in the context of COVID-19. Methods Our participants included a nationally representative sample of 2,619 young children (48.3% girls) and their primary caregivers (95.1% mothers) in Singapore. They were a subset of the participants in the Singapore Longitudinal Early Development Study (SG LEADS). Data were collected over two waves—before the outbreak of the COVID-19 pandemic (Wave 1) when these children aged 3 to 6, and during the second year of the pandemic (Wave 2). Primary caregivers completed measures of verbal cognitive ability, self-control, economic stress, and positive and negative parental control in Wave 1. Children’s self-regulation was assessed by the Delay of Gratification task in Wave 1, and their internalizing problems were rated by their primary caregivers in both waves. Other pre-pandemic family and community characteristics were collected as covariates. Structural equation modeling was performed. Results Pre-pandemic parental resources (i.e., verbal cognitive ability, self-control, and low economic stress) predicted children’s fewer internalizing problems during the pandemic and less aggravation of internalizing problems from before to during the pandemic, through more positive parental control (i.e., limit setting) and less negative parental control (i.e., harsh discipline). Moreover, children’s self-regulation during early childhood was predicted by their primary caregivers’ verbal cognitive ability and self-control, as well as positive parental control. Early childhood self-regulation further alleviated the aggravation of internalizing problems over time. Among the covariates, parental education, family income, parental psychological well-being, living with both parents, having a live-in domestic helper, and neighborhood quality also longitudinally predicted fewer child internalizing problems. Discussion Our findings underscore the importance of nurturing children’s emotional resilience under adverse and uncertain circumstances by boosting protective factors in their social-ecological system, including community-, family-, parent-, and child-level resources.